Development curriculum e-learning: Student engagement and student readiness perspective - Kuswandi, Dedi (2021)
The purpose of this study was to develop an online learning-based curriculum in terms of student engagement and student readiness, where the parameters used are the Indonesian National Qualifications Framework (KKNI) and the Curriculum of Learning Technology Study Programme. Curriculum development was carried out by integrating learning with the Learning Management System (SIPEJAR). The reason for using SIPEJAR as a learning system is because SIPEJAR is part of academic information systems and learning administration systems and offline and online learning service systems. Therefore, curriculum development can be easily implemented. © 2021 IEEE.